Priorities Towards Fair Allocation of Ventilators During COVID-19 Pandemic: A Delphi Study - Ghamari, Seyyed-Hadi; Abbasi-Kangevari, Mohsen; Zamani, Nasim; Hassanian-Moghaddam, Hossein; Kolahi, Ali-Asghar (Frontiers in Medicine, 2022)
Background: COVID-19 pandemic has resulted in severe shortage in vital resources, including invasive mechanical ventilators. The current imbalance between demand and supply of mechanical ventilators has called for investigations on the fair allocation of mechanical ventilators. Objective: To determine the priorities of the medical experts towards the fair allocation of ventilators during the COVID-19 pandemic. Methods: This study was conducted from May 28 to Aug 20, 2020. The questionnaire was sent to 50 medical specialists as the Delphi panel. Participants were asked to rate each prioritising factor: "-1" for low priority, "+1" for high priority, and "Zero" for equal priority. Results: Among 38 experts who responded to the email, the responses of 35 were analysed. 31(88.6%) participants recommended that pregnant women be considered high priority in allocating ventilators, 27(77.1%) mothers of children<5 years, 26(74.3%) patients under 80-years, and 23(65.7%) front-line-healthcare-workers. In contrast, 28(80.0) participants recommended that patients who are terminally ill should be considered as a low priority, 27(77.1%) patients with active-malignancy, 25(71.4%) neurodegenerative diseases, and 16(45.7%) patients aged>80. The panel did not reach a consensus regarding the role of patients' laboratory profiles, underlying diseases, or drug abuse in the prioritisation of ventilators. Conclusions: The panel considered pregnant mothers, mothers of children under five years, age groups younger than 80, and front-line healthcare workers to have high priority in allocating mechanical ventilators.